BCc1, a Chelation-Based Nanomedicine, modulates splenic cytokine networks toward a profile associated with antitumor immunity in 4T1 breast tumor–bearing mice - Moheb Afzali , Fereshteh; Heshmati , Masoumeh; Salimi , Ali; Kalanaky , Somayeh; Fakharzadeh , Saideh; Hafizi , Maryam; Esmail Akbari , Mohammad; Nazaran , Mohammad Hassan; Hashemi, Mehrdad (Archives of Advances in Biosciences, 2026)
Background and Aim: Breast cancer remains a major cause of cancer mortality in women, and tumor-driven cytokine dysregulation promotes immune escape. This study aimed to define the splenic immunomodulatory activity of BCc1 nanomedicine in 4T1 breast tumor-bearing BALB/c mice by measuring interleukin-12 (IL-12), transforming growth factor-β1 (TGF-β1), and tumor necrosis factor-α (TNF-α), and the (TGF-β1)⁄(IL-12) balance. Methods: Seventy female mice with palpable tumors received a 24-day regimen of intraperitoneal or oral BCc1, cyclophosphamide, or phosphate-buffered saline (PBS). Splenic cytokines were quantified by ELISA, and the (TGF-β1)⁄(IL-12) ratio was calculated as an index of cytokine polarization. Results: BCc1 reshaped splenic cytokine patterns in a dose- and route-dependent manner. High-dose intraperitoneal BCc1 produced the strongest effects, markedly reducing and , inducing controlled modulation of , and substantially lowering the ratio. These changes indicate reduced immunoregulatory dominance and a shift toward an antitumor-permissive cytokine milieu. For several cytokine endpoints, high-dose BCc1 showed effects comparable to or greater than cyclophosphamide. Oral BCc1 elicited milder dose-dependent responses, with stronger immunomodulation at the higher oral dose. Conclusion: BCc1 therefore mediates route- and dose-dependent splenic cytokine remodeling, supporting further evaluation as a multifunctional immunomodulatory nanotherapeutic; cellular phenotyping and functional antitumor assays are required to determine whether these cytokine shifts translate into immune-mediated tumor control Background and Aim: Breast cancer remains a major cause of cancer mortality in women, and tumor-driven cytokine dysregulation promotes immune escape. This study aimed to define the splenic immunomodulatory activity of BCc1 nanomedicine in 4T1 breast tumor-bearing BALB/c mice by measuring interleukin-12 (IL-12), transforming growth factor-β1 (TGF-β1), and tumor necrosis factor-α (TNF-α), and the (TGF-β1)⁄(IL-12) balance. Methods: Seventy female mice with palpable tumors received a 24-day regimen of intraperitoneal or oral BCc1, cyclophosphamide, or phosphate-buffered saline (PBS). Splenic cytokines were quantified by ELISA, and the (TGF-β1)⁄(IL-12) ratio was calculated as an index of cytokine polarization. Results: BCc1 reshaped splenic cytokine patterns in a dose- and route-dependent manner. High-dose intraperitoneal BCc1 produced the strongest effects, markedly reducing and , inducing controlled modulation of , and substantially lowering the ratio. These changes indicate reduced immunoregulatory dominance and a shift toward an antitumor-permissive cytokine milieu. For several cytokine endpoints, high-dose BCc1 showed effects comparable to or greater than cyclophosphamide. Oral BCc1 elicited milder dose-dependent responses, with stronger immunomodulation at the higher oral dose. Conclusion: BCc1 therefore mediates route- and dose-dependent splenic cytokine remodeling, supporting further evaluation as a multifunctional immunomodulatory nanotherapeutic; cellular phenotyping and functional antitumor assays are required to determine whether these cytokine shifts translate into immune-mediated tumor control